Structural discontinuties in the Witwatersrand group on the E.R.P.M. mine their geology, geochemistry and rock mechanics behaviour - Jeffrey, David George (My University, 2015)
The s t r u c t u r a l d i s c o n t i n u i t i e s ( d y k e s , f a u l t s , sh ear zones and j o i n t s ) found i n the E.R.P.M. a re d e s c r i b e d in terms o f t h e i r d i s t r i b u t i o n , p e t r o g r a p h y , g e o c h em is tr y and rock mechanics b e h a v io u r . F i v e groups o f dykes have been r e c o g n i s e d : o f p o s s i b l e Bushveld age ar e a m e l a n o r i t e d y k e / s i l l (The Simmer Dyke) and a swarm o f i l m e n i t e d i a b a s e s , and o f p o s s i b l e V e n t e r sd o ip age are "wo s e t s o f 030 s t r i k i n g t h o l e i i t i c q u artz d o l e r i t e s and a s e r i e s o f e a s t - w e s t s t r i k i n g u l t r a n y I o n i t e zones t h a t are g e o c h e m i c a l l y shown to be ciykes. The g e o c h e m i s tr y shows a l l th e dykes to be t h o l e i i t i c and g e n e r a l l y a l k a l i poor. F a u l t i n g i n the mine i s c h a r a c t e r i s e d by complex r o t a t i o n a l movements. R o t a t i o n a l f a u l t i n g , f a u l t t e r m i n a t i o n s , f a u l t f i l l s and s h e a r zones are d i s c u s s e d . Three groups o f f a u l t s are d e s c r i b e d : one s e t which di ps sout h and s t r i k e s p a r a l l e l to the s e d i m e n t s , prob abl y formed during the form atio n o f the b a s i n but they have s i n c e been r e a c t i v a t e d t o r e v e r s e f a u l t s . The o t n e r two g r o u p s , one o f which shows a s i n i s t r a l s t r i k e - s l i p d i s p la c em en t and the o t h e r a d e x t r a l s t r i k e - s l i p d i s p l a c e m e n t , ^orm a c o n j u g a te p a i r . D e t a i l e d d e s c r i p t i o n s o f both o r i g i n a l and mining induced j o i n t i n g ar e g i v e n , th e i n f l u e n c e o f s t r u c t u r a l d i s c o n t i n u i t i e s on j o i n t i n g d i s t r i b u t i o n i s d i s c u s s e d and some mechanisms o f form at io n are pro po sed. Fi ve s e t s o f o r i g i n a l j o i n t i n g and two main ty p es o f mining induced f r a c t u r i n g a r e r e c o g n i s e d . Re gion al l i f l e a t i o n p a t t e r n s a re a n a l y s e d and i t i s found that, th e main r e g i o n a l tre n d s are s i m i l a r t o th e l o c a l E.R.P.M. t r e n d s . A dynamic a n a l y s i s of th e s t r u c t u r a l d i s c o n t i n u i t i e s i s d e s c r i b ' d and a s t r e s s h i s t o r y , on bo th a r e g i o n a l and l o c a l s c a l e , i s prop osed. A d e t a i l e d ro ck mechanic s tu d y of f o u r l a r g e dykes i n the mine i s d i s c u s s e d ; s pe cim ens have been t e s t e d i n both u n i a x i a l and t r i a x i a l com pre ssion and the u n i a x i a l c om p re ssiv e s t r e n g t h , roung s Modulus, P o i s s o n ' s R a t i o , u n i a x i a l t e n s i l e s t . i n g t h , i n t r i n s i c s h e a r s t r e n g t h and a n g l e and c o e f f i c i e n t o f i n t e r n a l f r i c t i o n have b e e n determined f o r v a r i o u s sp e c im e n s . I n the f i n a l c h a p t e r , the e f f e c t s o f s t r u c t u r a l d i s c o n t i n u i t i e s on th e d i s t r i b u t i o n o f r o c k b u r s t s and s e i s m i c e v e n t s i s d i s c u s s e d . The r e s u l t s i n d i c a t e t h a t the d i s t r i b u t i o n of s e i s m i c e v e n t s i s not c o n t r o l l e d by the s t r u c t u r a l d i s c o n t i n u i t i e s but some dykes do c o n t r o l the d i s t r i b u t i o n of r o c k b u r s t s .
A Dissertation Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg for the Degree o f Master of Science Johannesburg 1975.